Effect Of Strength On Cotton And Blended Mattress Fabric Produced By Mechanical Processing System - Azad, Md Abul Kalam; Jafrin, Shamina; Haque, Md Tahzibul (Daffodil International University Journal of Science and Technology, 2011)
Mattress fabric is one time used fabric. It need not require for washing. In this perspective, a project was taken to replace 100% cotton mattress fabric instead of Jute-Cotton blended mattress fabric. It is seen that Jute: Cotton blended mattress fabric posses similar properties to the 100% cotton mattress fabric. Bursting strength is an important factor for mattress fabric. From the comparison result, it is also seen that the bursting strength of 80:20/Jute: Cotton blended mattress fabric is nearer to the 100% cotton mattress fabric. On the other hand, blended mattress fabric is cheaper than 100% Cotton mattress fabric. Hence, blended mattress fabric may be the replacement of 100% cotton mattress fabric. Keywords: Strength; Mattress; Jute-cotton Union; Mechanical; Warpwise; Waftwise; Bursting. DOI: http://dx.doi.org/10.3329/diujst.v6i2.9340 DIUJST 2011; 6(2): 11-13